Pengaruh Kualitas dan Nilai Pelayanan Terhadap Kepuasan Mahasiswa - Sudarmi, Sudarmi; Ridjal, Syamsul; Djumadi, Edy (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to examine the impact of service quality and value on student satisfaction. This research was conducted using a quantitative approach conducted on 96 university students with active status in the academic year 2023-2024 odd semester who were at the stage of completing their studies, this was done with the consideration that these students had obtained all academic services available at the Makassar Bongaya College of Economics. Hypothesis testing utilised multiple linear regression analysis with the help of SPSS Ver. 27. The results of hypothesis testing provide evidence that service quality is linearly related to student satisfaction variables, the quality of academic administration services that are good and perceived by students is proven to increase student satisfaction. Service value (emotional value, social value, and service performance value) has a significant positive impact on student satisfaction. This is because the emotional value shown by academic administration staff is very good at serving students, that the better the value of service, the higher the satisfaction felt by students.